Internalization Of Pencasila Values In The Practice Of Islamic Religious Education Through Learning Aqidah Akhlak At Sdn Gempeng II Bangil - Insani, Meydiana Firda; Mubarok, Achmat (AR-RASYID : Jurnal Pendidikan Agama Islam, 2025)
This study aims to explore the application of Pancasila values in Islamic Religious Education (PAI) through Aqidah Akhlak learning at SDN Gempeng II Bangil. The method used is a case study with a descriptive approach, involving observation, interviews, and documentation to collect data. The results showed that Pancasila values were internalized through various methods, such as discussions, exemplary stories, and direct practice. Students showed improved understanding and application of the values in daily life. However, challenges such as low student motivation and differences in social background need to be overcome. In conclusion, the internalization of Pancasila values in Aqidah Akhlak learning at SDN Gempeng II Bangil is effective, but requires support from various parties to optimize the character education process.